Effects of Crude Protein Levels on Growth Performance, Nitrogen Balance, Digestibility and Crude Protein Requirement of Growing Fuxing Pig - Yunce Cai; Shengchang Chen; Jingshang Li; Xiaoluo Lu; Shengyong lu; Haixia Li; Yan Zhang (Journal of Animal and Plant Sciences, 2024)
(Objectives)The objective of this study was to determine the protein requirement of growing Fuxing pig, and provide basic parameters for the determination of the feeding standards of growing Fuxing pig.( Methodology)A single factor randomized block design was used in this experiment, and forty healthy weaned pigs with body weight of(20.45±1.65kg)were selected randomly and divided into 4 groups, 10 heads of each. Each group was fed dietary of CP levels(CP12?CP14?CP16?CP18)respectively in 67 days feeding trail, 7 days preliminary experimental period and 60 days experimental period. Three health pigs are randomly selected from each group, all urine and feces were selected to determine the nutrition digestibility and metabolic rates before the last 7 days experiment.( Main results)The results showed that adding CP16 to the diet could reduce the F/G, and the CP16 group decreased by 8%, 6.9%, and 3.7% compared with that of the CP12, CP14, and CP18 groups, respectively. There was no difference between the CP16 and CP18 groups (P>0.05). The digestibility of EE in the CP16 and CP18 groups was significantly higher than that in the CP12 group (P<0.05), and it was not significantly different between the CP14, CP16, and CP18 groups (P>0.05). With the increase of crude protein levels, The digestibility of EE in the CP, DCP (digestible crude protein) CP16and CP18 groups was extremely significantly higher than the CP12 group, CP14 group (P<0.01), CP16 group NI (nitrogen intake), UN (urine nitrogen), RN (retention nitrogen), N%, all significantly higher in the CP12 group, CP14 group.(Conclusions)In summary, Fuxing pig DCP intake was used as the dependent variable (Y) and ADG as the independent variable (X) for linear regression analysis, the digestible CP requirement the regression equation with Fuxing pig's growing period is as follows: DCP=1.93 W0.75+0.34?W (DCP: g/d;W0.75: kg;?W: g/d).
Keywords: Fuxing Pig; Protein Requirement; Growth Performance; Nitrogen Balance; Regression Model